Study the Effect of High HbA1 Levels on Kidney and Liver Function - El-Mahdi Mohamed,; Hanan Moftah,; Alnagy Mohammed,; Marfoua Ali, (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aims. Diabetes is a chronic illness. The comorbidities that can be linked to elevated blood sugar levels must be understood. The purpose of this study was to evaluate the impact of elevated hemoglobin subunit alpha 1 (HbA1) on renal and hepatic functioning in individuals with diabetes in Al-Jabal Al-Akhdar, Libya. Methods. From January to December 2022, blood samples from18 patients with high HbA1 level and 37 with normal values were analyzed in the laboratories located in Al Bayda city, Libya. Results. According to the findings, patients with high HbA1 levels had higher results on tests measuring liver function, but these increases were not statistically significant when compared to participants with normal HbA1 levels. Additionally, there were notable variations between the first and second groups' glutamic Oxaloacetic transaminase enzyme levels. Conclusion. HbA1 should only be assessed in conjunction with fasting plasma, post-meal glucose, liver and kidney function tests for accurate monitoring of diabetes patients' long-term glycemic management.